Harmonization of Law Enforcerment and Gender Juctice: The Crisis for Divorce Lawsuits in Domestic Violence - Fikri Fikri; Aris Aris; Muhammad Munzir; Mutiara Mutiara (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
The purpose of this study is to reveal that divorce is contested as a result of domestic violence that has exceeded the limit, so that it is considered a crisis and crucial in family problems. There are two problems, namely how the judge considers in making a decision on a contested divorce case, and how to uphold the law and justice in a contested divorce case. Data analysis was carried out using the theory of law enforcement and gender justice, using a socio-anthropological approach. The results show that the consideration of judges in deciding divorce cases as harmonization in law enforcement is that the husband's position in the household. He cannot commit arbitrary acts and physical, psychological, sexual and financial violence, excessive burdens on wives, as the implementation of gender justice. Harmonization of law enforcement and gender justice in divorce cases is realizing and protecting the rights of wives with equal position with husband so they don't continue to be victims of violence, not in a marginal position in the household. This research can be recommended to continue to do research that is more perfect in uncovering cases of divorce due to domestic violence.